The SAGE encyclopedia of educational technology - Spector, J. Michael (Thousand Oaks, California : SAGE Publications, 2015)
This SAGE encyclopedia examines information on leveraging the power of technology to support teaching and learning. While using innovative technology to educate individuals is certainly not a new topic, how it is approached, adapted, and used toward the services of achieving real gains in student performance is extremely pertinent. This reference explores such issues, focusing on core topics and issues that will retain relevance in the face of perpetually evolving devices, services, and specific techniques.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 12, 2015).
Keywords: Educational technology -- Encyclopedias